Exercise and diseases prevention through training - Radak, Zsolt (Meyer & Meyer Sport, 2005)
Regular exercise increases the average life span and the quality of life. These effects are mediated by the fact that regular exercise is preventive to a number of diseases. This work covers the effects of exercise on the most common health threatening diseases